Search Frictions, Financial Frictions and Labor Market Fluctuations in Emerging Economies - Sumru Altug; Serdar Kabaca; Meltem Poyraz (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
This paper examines the role of the extensive and intensive margins of work in the context of business cycles in emerging markets with a financial friction. The earlier literature analyzed the role of search frictions with only an extensive margin of work and showed that such a framework can address the distinguishable business-cycle characteristics of emerging markets such as highly volatile consumption, countercyclical net exports, highly volatile wages and pro-cyclical wages. One of our contributions is to show that in the presence of an endogenous hours choice, search frictions fail to predict not only these characteristics but also the positive co-movement of hours worked per worker and employment with output. This occurs due to the strong income effect on hours worked. On the other hand, introducing a financial friction, namely working capital, significantly increases the performance of the model and suggests frictions in both labor markets and financial markets are necessary for explaining emerging market business cycles.
Keywords: F41; E44; J40; 330; search frictions; emerging markets; business cycles; working capital